2007
DOI: 10.1002/ibd.20040
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T lymphocytes mediate colitis in HLA-B27 transgenic rats monoassociated with nonpathogenic Bacteroides vulgatus

Abstract: These results implicate CD4(+) T cells in the development of colitis in HLA-B27 TG rats monoassociated with the nonpathogenic bacterial strain B. vulgatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…It was recently reported that all of the disease features develop unimpeded in B27/hß 2 m transgenic rats lacking a functional CD8a gene, despite profoundly impaired CTL responses 83 . Similar results have been observed in cell transfer and depletion experiments 84,85,86 . To the extent that the rat model mirrors the role of B27 in human SpA, these results challenge the hypothesis that CD8+ T cell recognition of B27 is central to disease pathogenesis.…”
Section: Hla-b27 Transgenic Ratssupporting
confidence: 91%
“…It was recently reported that all of the disease features develop unimpeded in B27/hß 2 m transgenic rats lacking a functional CD8a gene, despite profoundly impaired CTL responses 83 . Similar results have been observed in cell transfer and depletion experiments 84,85,86 . To the extent that the rat model mirrors the role of B27 in human SpA, these results challenge the hypothesis that CD8+ T cell recognition of B27 is central to disease pathogenesis.…”
Section: Hla-b27 Transgenic Ratssupporting
confidence: 91%
“…Conflicting data exist on the role of B. vulgatus in the pathogenesis of IBD. Germ-free rats transgenically expressing HLA-B27, a human MHC class I allele linked to spondyloarthritis-associated IBD (Brakenhoff et al, 2010), developed T-cell dependent colitis when colonized with B. vulgatus but not with various other bacteria including E. coli (Hoentjen et al, 2007; Rath et al, 1999). Interestingly, E. coli but not Bacteroides species were enriched in the intestines of conventionally raised, spontaneously colitic transgenic rats (Onderdonk et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…If these HLA-B27 transgenic animals were kept in a germ-free environment, they did not develop arthritis. Recolonization of the gut with Bacteroides vulgatus resulted in inflammatory changes [50,51]. However, introducing Lactobacillus and fusiform bacteria to the gut of germ-free animals had shown no such effect.…”
Section: Contribution To Diseasementioning
confidence: 99%